LEGAL CHARACTERISTICS OF THE OBJECT AND OBJECTIVE SIDE OF THE CRIME – LOGGING - Piskun, Ivan; Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to investigate the concept and carry out a legal characterization of the object and the objective side of the crime - "looting", as well as to carry out a systematic analysis of the features of the legal structure of the criminal offense - "looting". Research methods: constitute the main methods and means of knowledge, such as: documentary analysis and synthesis, comparison, objective truth, cognitive-analytical, interdisciplinary method of legal research, generalization. Results: the concepts and features of the legal composition of the object and the objective side of the criminal offense - "looting" were comprehensively analyzed. Discussion: the object and the objective side of the criminal offense - "looting" are mandatory parts of the legal structure of the criminal offense, without which the criminal offense is not valid, the objects of the criminal offense of "looting" and the objective side of looting are defined should be considered as the external situation of the person before the committed crime. The author concludes that looting is a serious violation of the law that poses a threat to public safety and violates the rights and interests of civilians in crisis situations and military conflicts. It reflects a phenomenon of lawlessness and disorder that can lead to serious consequences for society and its members. Appropriate criminal sanctions and anti-looting measures are important to ensure law and order and protect civil rights in a crisis. It is also important to uphold humanitarian norms and international law in these situations. In conclusion, the most effective way to combat looting is through a comprehensive approach involving joint efforts by law enforcement, military and civilian institutions. This will ensure security and order in crisis situations.